Othello Syndrome Secondary to Ropinirole: A Case Study - Kakali Pal; Abigail Smith; Joseph Hayes; Apu Chakraborty (Case Reports in Psychiatry)
This case report describes a forty-two-year-old man with no previous psychiatric history who developed delusional jealousy (Othello Syndrome) associated with ropinirole treatment. Ropinirole is a commonly used dopamine receptor agonist, which was being used to treat his Parkinson’s disease, and his delusional symptoms resolved entirely with ropinirole dose reduction.